An Appraisal of Conceptual Replica of Interlinkages between Infrastructure, Services and Sustainable Tourism at Destinations - Gowhar Ahmad Wani (Centre For Tourism Planning and Development, 2022)
This paper explored conceptual replica of interlinkages between infrastructure, services and sustainable tourism. The major perception is to develop a conceptual replica and lay solid foundations for future research. Infrastructure problems have a wide-ranging impact on service delivery and quality assurance, increasing the problem of tourist destination sustainability. The sustainable infrastructure and services are crucial in putting sustainability practices in place. Destinations with poor infrastructure and services generate a slew of negative externalities that jeopardise their long-term viability. For methodology, the models and theories related to concepts described above are taken from standard data webs of Elsevier, J store, Taylor and Francis, Emerald, SAGE, ABDC journal papers, Springer, and MDPI. The theoretical framework confirms strong relations and recommends further scientific investigations. It is inferred that the better infrastructure and standard services could be beneficial for tourism stakeholders in ensuring the better operation of sustainable tourism at destinations. As a result, broad opportunities for empirical research are generally brought into the light to help researchers for further studies.